Ein dynamischer Zugang zu „einfachen“ algebraischen Kurven (mathematica didactica, 2002)
Despite its low relevance for teaching the desideratum „Algebraic curves“ has always been an issue within mathematical didactics. This article aimes to continue this tradition by applying current dynamic geometry software (Cabri II+) and with respect to a project oriented mathematics instruction.